The Influence of HR Competence, Work Discipline and Organizational Commitment on ASN Performance in the Regional Development Planning Agency South Barito Regency - Asrul Nirman; Ramadhan, Ramadhan (Jurnal Multidisiplin Sahombu, 2022)
This research aims to determine and analyze the influence of human resource competence, work discipline and organizational commitment on employee performance. T his quantitative research uses multiple linear regression analysis method. The independent variables are human resource competence, work discipline, and organizational commitment then the dependent variable is employee performance. Respondents in the research are employees in the regional development planning agency of South Barito using a saturated sample technique consisting of 44 people. This research uses data collection method by interview, questionnaire and literature study. The method of analysis used in this research is using descriptive and multiple linear regression analysis by SPSS. The results of this research influences are (1) human resource competence, work discipline and organizational commitment have positive correlation and significant simultaneous influence to employee performance; (2) human resource competence, work discipline and organizational commitment have positive correlation and significant partial influence to employee performance; (3) human resource competence is the dominant variable between work discipline and organizational commitment on employee performance in the regional development planning agency of South Barito.